Current status of CO2 capture with ionic liquids: Development and progress - Wamda Faisal Elmobarak (17831939) (2023)
Global warming triggered by greenhouse gas (GHG) emissions, particularly carbon dioxide (CO2), significantly influences climate change and has become a common environmental issue recently. The current amine-based technologies (ABTs) for CO2 capture ( CAPCO2 ) have high energy demand, low absorption, and desorption rates, and are less environmentally sustainable due to high emissions of volatile solvents. Therefore, the development of environmentally friendly CAPCO2 materials and/or processes is a growing area of research. The utilization of ionic liquids (ILs) for CAPCO2 has recently attracted attention. The unique characteristics of ILs, such as their low vapor pressure and high affinity for CAPCO2 as well as their low volatility make them a viable substitute for the existing processes. This work provides a comprehensive overview of the accomplishments and challenges during the use of ILs for CAPCO2 . The Review also outlines the mechanisms of the CAPCO2 with ILs at the molecular level, the properties of ILs, characterization of the CO2/IL systems, and the effect of operating conditions on CO2 uptake (UPCO2) capacity by ILs. It also emphasizes the impact of cations, anions, and functional groups on the solubility of CO2 (( SCO2 ) ) in ILs as well as the biodegradability and toxicity of ILs. Additionally, recent advances in IL membrane technology for the CAPCO2 processes are considered. Lastly, the contribution of molecular simulations to create and assess ILs was reviewed. Protic and aprotic ILs properties have shown outstanding efficiency of UPCO2 . The interactions between the anionic part of IL and CO2 enhance the UPCO2 and outperform the efficiency of traditional organic solvents. Functionalized ionic liquids (FUNILs) with tuned functional groups, supported ionic liquids membranes (SILMs) as well as reversible ionic liquids (RILs) have improved the efficiency of ILs as a promising CO2 capturing process from industrial streams even under low CO2 partial pressure. The relative importance of the chemical breakdown of the IL constituents (cation–anion interfacial structuring) during the CAPCO2 process at different operating temperatures is unclear, and more research in this area is required to better inform the design of new ILs. This review provides a proper/systematic guideline to help ILs manufacturers and engineers design high-capacity ILs for appropriate CAPCO2. Other Information Published in: Fuel License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.fuel.2023.128102